THE EFFECT OF WORK MOTIVATION, COMPETENCY AND AFFECTIVE COMMITMENT ON PERFORMANCE OF CIVIL SERVANTS OF THE TNI-AD IN THE FIELD ARTILLERY WEAPONS CENTER (PUSSENARMED) IN CIMAHI - Khansa Nur Agustin Febyanti; Irawan Budi Utomo; Aceng Abdul Hamid (Journal Of Resource Management, Economics And Business, 2023)
Purpose: This study aims to analyze the influence of work motivation, competence, and affective commitment on the performance of civil servants at the Indonesian Army's Center for Artillery Forces (PUSSENARMED) in Cimahi. Research Methodology: This research employs multiple linear regression analysis to examine the relationships among these variables. Data were collected through questionnaires distributed to 33 civil servant respondents at PUSSENARMED. Results: The findings indicate that work motivation has a significant positive influence on PNS performance; the higher the motivation, the better their performance. Competence shows a relatively low negative influence on performance, while affective commitment has a significant positive influence. Simultaneously, all three independent variables provide a significant influence on PNS performance, explaining about 51.4% of the variation in performance Limitations: This study is limited to one institution, namely PUSSENARMED in Cimahi, so the results may not be generalizable to other institutions. Contribution: These findings can be utilized to enhance human resource management in the public sector, particularly within the military context, with a focus on improving work motivation and employee affective commitment.